Restorasi Bisnis Olahan Komoditas Bambu melalui Teknologi Tepat Guna Pirolisis Anaerob dan Teknik Kondensasi Berwawasan Agrosociopreneur - Prabowo, Rachmat; Saleh, Chairul (Program Studi Agribisnis, 2025)
The development of bamboo as an alternative biomass source holds strong potential to address the shortages of charcoal raw materials while enhancing village-level economic productivity. However, charcoal production in Mengok Village is still dominated by traditional open-burning methods that are inefficient, produce inconsistent charcoal quality, require long processing times, and generate high emissions. This study aims to identify the technical and managerial needs of KUB Kartika Jaya and KUB Mengok Jaya through a needs assessment, develop an anaerobic pyrolysis prototype equipped with a condensation system, and formulate a business development model using the Social Business Model Canvas. The research applied a descriptive–analytic approach supported by interviews, observation, and focus group discussions. Findings indicate that the primary technical needs include temperature control, standardized raw-material preparation, and closed-system combustion. Managerial needs encompass formal organizational structure, production bookkeeping, and operational SOPs. The anaerobic pyrolysis prototype demonstrated improved combustion efficiency and more consistent charcoal quality. The resulting social business model illustrates that the technology enhances income, strengthens institutional capacity, and contributes positively to environmental sustainability. This study highlights the importance of integrating technological innovation with social empowerment in developing rural biomass enterprises.